Enteric Delayed-Release Granules Loading Dendrobine Ameliorates Hyperlipidemia in Mice by Regulating Intestinal Flora Composition - Shunqiang Song; Liangyu Yang; Tingting Chen; Yongai Xiong (Pharmaceutics)
Background/Objectives: In this paper, we created enteric delayed-release granules that load Dendrobine (DNL) directly into the intestinal flora of hyperlipidemic mice, based on the relationship between intestinal flora and hyperlipidemia. Methods: We then used pharmacodynamics and 16 Sr RNA high-throughput sequencing to examine the hypolipidemic effects and mechanism of these granules. Solvent evaporation was used to create the DNL, which was then characterized using FT–IR, XRD, SEM, and DSC. A high-fat diet was used to create the mouse model of hyperlipidemia in C57BL/6J mice. Dendrobine, various dosages of DNL, TMAO, and the combination of TMAO and DNL were subsequently gavaged on the mice. The makeup of the intestinal flora in the mouse colon was analyzed using 16S rRNA sequencing, and the effectiveness and mechanism of DNL in controlling the intestinal flora for the treatment of hyperlipidemia in mice were investigated. Results/Conclusions: The findings showed that DNL could effectively improve the dysbiosis brought on by hyperlipidemia by significantly lowering the mice’s body weight and blood lipid level (p < 0.05), while also regulating the function of their intestinal flora, increasing the abundance of Actinobacteria (p < 0.05) and Thick-walled bacterium (p < 0.05), and decreasing the abundance of Desulfovibrio (p < 0.05) and Mycobacterium anisopliae (p < 0.05) in the intestinal flora of mice, inhibiting the growth of intestinal harmful microorganisms, providing space for the reproduction of beneficial bacteria, and thus maintaining the stability of the intestinal flora’s structure.